Aswq al-auraq al-maliyah wa dauruha fi tanwil al-tanmiyah al-iqtishadiyah ... - RIDLWAN, Samir Abdulhamid (Al-Ma'had Al-Alamy, Kairo, 1996)
Aswaq Al-auraq al-maliyah wa daruha fi tamwil al-tanmiyah al-iqtishadiyah ...